2005
DOI: 10.1152/ajpcell.00299.2004
|View full text |Cite
|
Sign up to set email alerts
|

CaM kinase II and phospholamban contribute to caffeine-induced relaxation of murine gastric fundus smooth muscle

Abstract: Caffeine has been shown to increase the Ca(2+) release frequency (Ca(2+) sparks) from the sarcoplasmic reticulum (SR) through ryanodine-sensitive stores and relax gastric fundus smooth muscle. Increased Ca(2+) store refilling increases the frequency of Ca(2+) release events and store refilling is enhanced by CaM kinase II (CaMKII) phosphorylation of phospholamban (PLB). These findings suggest that transient, localized Ca(2+) release events from the SR may activate CaMKII and contribute to relaxation by enhanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 60 publications
5
39
0
Order By: Relevance
“…Others have previously shown that ryanodine partially reverses the caffeine relaxant effect in adult rat fundic muscle (15). As shown in Figure 3b, ryanodine reversed the caffeine-induced relaxation by 36% (P < 0.01), an inhibitory effect of similar proportions to the one previously reported in adult rat tissue (15).…”
Section: Caffeine Reduces Gastric and Intestinal Muscle Tonesupporting
confidence: 82%
See 4 more Smart Citations
“…Others have previously shown that ryanodine partially reverses the caffeine relaxant effect in adult rat fundic muscle (15). As shown in Figure 3b, ryanodine reversed the caffeine-induced relaxation by 36% (P < 0.01), an inhibitory effect of similar proportions to the one previously reported in adult rat tissue (15).…”
Section: Caffeine Reduces Gastric and Intestinal Muscle Tonesupporting
confidence: 82%
“…The caffeine effect is not age-dependent such that this compound equally reduces the esophageal and gastrointestinal muscle tone of adult rats. The mechanism responsible for the caffeine-induced gastrointestinal muscle tone in the newborn is mediated via smooth muscle cell ryanodine receptors, as previously shown in adult rat tissue (15). To the best of our knowledge, this is the first English literature report addressing the effect of caffeine on the gastrointestinal muscle tone early in life.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations